Empire, race and global justice - Bell, Duncan 1976- (Cambridge University Press, 2019)
"Abject poverty. Yawning inequality, political, economic, and social. Human rights and their systematic abuse. Nationality, sovereignty, citizenship. The identification of historical injustices and their possible rectification. Migration flows and border politics. The legitimation, conduct, and cessation of war. Terrorism, terror, territory. Democracy beyond and between states. All of these topics and more are addressed in contemporary debates over global justice. They have motivated activism, spawning social movements, political protest, and legal campaigns. They are debated across a range of academic disciplines and discourses: sociologists, International Relations (IR) scholars, geographers, anthropologists, economists, and historians, have contributed important work on the subject. In political theory, global justice has been a core topic at least since the end of the cold war, its meaning, scope, and policy implications contested by groups of egalitarian cosmopolitans, libertarians, liberal nationalists, and statists, among others. The importance of the subject shows no sign of waning"...